Sistem Pengontrolan Antena Penerima TV Menggunakan Arduino - Dyah Vitalocca; Muliadi Muliadi; Dyah Darma Andayani (Seminar Nasional LP2M UNM, 2019)
Abstract. The TV receiver antenna control system using arduino. This research aims to design a television Antenna Control System using Arduino. This type of research is experimental research.Data retrieval is done by setting the angle of the antenna of the receiver towards the antenna the antenna control system uses transmitters of television for each Television channel.The results showed that the control of television antenna system using arduino can be used to control the direction of the antenna on the right position according to the television transmitters received layout so that the quality of image and sound transmitter television is received well Keywords: receiver, antenna control system, arduino